Impact of Machining Parameters on Wire Arc Additively Manufactured Mild Steel Specimens of E6013 and E7018 Using an Electric Arc Heat Source - Muhammad Muzamil; Nabeel Ahmed Siddiqui; Kamal Kumar; Ghulam Hussain; Mohammed Alkahtani; Mohsin Sattar (Crystals)
This study investigates the machining parameters that affect the surface roughness of additively manufactured specimens employing wire arc additive manufacturing (WAAM) using electric arc welding as a heat source. The specimens were prepared using E6013 and E7018 filler rods for layered deposition on a mild steel base plate. For the machining operation, two variable parameters, cutting speed and depth of cut, were selected and coded as high (480 RPM, 0.5 mm depth) and low (310 RPM, 0.25 mm depth) while keeping the feed rate constant. The study employed a 2k factorial design of experiment (DOE) using Minitab software to assess the impact of parameters and their levels on the output response of surface roughness. Analysis of variance (ANOVA) results show that cutting parameters like cutting speed and their interaction with the depth of cut significantly affect surface quality. The experimental data were also used to develop polynomial model response equations for predicting surface roughness. This study firmly demonstrates the critical role of machining parameters in enhancing the surface quality of low-cost additively manufactured components using an electric arc welding heat source.